Comparative pharmacokinetic analysis of levonorgestrel-releasing intrauterine systems and levonorgestrel-containing contraceptives with oral or subdermal administration route. (1st November 2020) - Hofmann, Birte Maria; Apter, Dan; Bitzer, Johannes; Reinecke, Isabel; Serrani, Marco; Höchel, Joachim; Merz, Martin
Abstract: Objective: To compare systemic exposure to levonorgestrel (LNG) released from commercially available intrauterine systems (IUSs), a subdermal implant, and oral contraceptives. Methods: An integrated population pharmacokinetic (popPK) analysis of data from over 3400 individuals in ten clinical studies with six different LNG-releasing contraceptives (four long-acting reversible contraceptives [LARCs: LNG-IUS 8, 12, and 20, initially releasing LNG 14, 17.5, and 20 μg/day, a subdermal implant initially releasing LNG 100 μg/day according to label]; progestin-only pill [POP: LNG 30 μg/day]; and combined oral contraceptive [COC] pill [LNG 100 μg/day and ethinylestradiol 20 μg/day]), was conducted to generate a popPK model. LNG release rates, and total and unbound serum/plasma LNG concentrations with LARCs were estimated over the indicated period of use; maximum (Cmax ) and average (Cav ) serum LNG concentrations were estimated at steady state for oral contraceptives. Influence of body weight on LNG PK was also investigated. Results: Serum LNG concentration with LARCs increased with increasing daily LNG release rate, being lowest with LNG-IUS 8, higher with LNG-IUS 12 and LNG-IUS 20, and highest with the subdermal implant (1.7–2.1-times that with LNG-IUS 20). Compared with early serum LNG concentrations with LNG-IUS 20, Cav and Cmax were 1.7- and 4.5-fold higher with POP, and 8.6- and 18-fold higher with COC. Total LNG bioavailability was >97% for the LNG-IUSs and 66–80% with other contraceptives. Serum/plasma LNG concentrations decreased with increasing body weight. Conclusions: Among the contraceptives examined, COC had the highest and LNG-IUSs the lowest systemic exposure to LNG. Systemic LNG concentration was inversely correlated to body weight.